Seismic Evaluation of New Steel Infill Panels for Steel Shear Walls - Ali Joharchi; Siti Aminah Osman; Mohd Yazmil Md Yatim; Mohammad Ansari (Civil Engineering Journal, 2021)
Corrugated Steel Shear Wall (CSSW) is an efficient shear wall system, which has higher energy dissipation capacity, ductility and stiffness when compared to the Steel Plate Shear Wall (SPSW) with flat infill plate. Despite of these advantages, the ultimate load of CSSW is lower than that of SPSW. Various studies conducted to improve the cyclic behavior of CSSW revealed that increasing corrugation angle might enhance energy dissipation capacity and toughness of CSSWs. However, the ultimate load of CSSW was not improved by increasing the corrugation angle. Thus, the current study proposed new corrugated infill panel schemes to improve the ultimate load of CSSWs. To this end, Finite Element (FE) models were established using ABAQUS/Standard and verified with the experimental results from previous researches. The corrugation angle of the proposed plates was found based on a numerical investigation on seven CSSW FE models with the corrugation angle ranges from 30° to 120°. The FE results revealed that the model with the corrugation angle of 120 achieved highest ultimate load, energy dissipation capacity and toughness amongst the CSSW models. In addition, the ultimate loads, energy dissipation capacities and toughness of the proposed infill plates were up to 11.8%, 53.9% and 8.8% respectively higher than those of CSSW model with the corrugation angle of 120°. Furthermore, the proposed infill plates use up to 13.4% lower amount of steel compared to the corrugated plate with the corrugation angle of 120. Doi: 10.28991/cej-2021-03091678 Full Text: PDF